Formulation of anxiety concentration index on athletes performances using application of IoT device - Wan Nurlisa, Wan Ahmad; Mohd Azrul Hisham, Mohd Adib; Mohd Husaini, Mohd Jaafar; Sut Txi, Mon Redee (IJETAE Publishing House, 2023)
Competitive anxiety is the greatest challenge for athletes, especially in games involving big competitions. This study aims to formulate athletes' anxiety based on their sports performance. Therefore, this study found three parameters influencing athletes' anxiety: heart rate, blood pressure and muscle tension. Hence, the data collection from three phases, namely before, during and after the competition, was recorded. The data were analyzed based on the anxiety index formulation to obtain the athletes' anxiety index rate. By comparing the reading pace of normal persons to the results of this data analysis, the researcher created a set of athlete anxiety indexes. For future research, an anxiety monitoring system prototype based on IoT technology will be created using coding from the athlete's anxiety index to ensure that the coach can notice the athlete's anxiety rate early. With this study, it is believed that future sports athlete performance in the country will be more consistent.